Efficacy of intravenous vitamin C in management of moderate and severe COVID-19: A double blind randomized placebo controlled trial - Vijay Kumar; Divendu Bhushan; Sushmita Supriya; Avinash Aravind Ganapule; Pallavi Lohani; Shyama; Sanjay Pandey; Pramod Kumar Majhi; Utpal Anand; Ramesh Kumar; Umesh Kumar Bhadani (Journal of Family Medicine and Primary Care, 2022)
Aim: To study the efficacy of intravenous vitamin C in management of moderate and severe COVID-19. Objective: To determine the efficacy of intravenous vitamin C in reducing in-hospital mortality in moderate and severe cases of COVID-19. Design: Parallel, double-blinded randomized controlled trial with placebo. Ethical clearance was obtained from the institutional ethics committee, AIIMS Patna. The trial was registered with the Clinical Trials Registry – India (registration number- CTRI/2020/11/029230.) Setting: A tertiary care centre in Bihar, India Participants: All patients above the age of 18 years both males and females, admitted in ICU with a diagnosis of moderate and severe COVID-19 (on the basis of a positive reverse transcriptase polymerase chain reaction (RT–PCR) report) at our facility during the study period (01/10/2020–31/12/2020) not having any of the exclusion criteria. Intervention: The patients in the intervention arm were given 1 gram (2 ampoules of 2 ml each containing 500 mg of vitamin C mixed in 100 ml normal saline) intravenous vitamin C 8 hourly for four days. The patients in the placebo arm received similar looking ampoules (2 ampoules of 2 ml sterile water for injection mixed in 100 ml normal saline) intravenously 8 hourly for four days. The rest of the treatment was given as per the standard operating procedure (SOP) of the institute with adjustments as per treating team's judgement. Outcome Measures: Primary outcome was reduction in in-hospital mortality. Secondary outcomes were improvement in qSOFA score, pO2/fiO2 ratio, fall in inflammatory markers, need for mechanical ventilation and vasopressors. Results: Regarding primary outcome, 10 (33.3%) patients died in intervention group compared to 13 (43.3%) in placebo. Worth noting from baseline characteristics is that 86.7% in intervention arm were of severe category compared to 66.7% severe category patients in placebo group. Though number of severe cases were more in intervention arm there has been comparatively less mortality in this group. Regarding secondary outcomes, amongst 30 patients in vitamin C group, 11 (36.7%) required invasive mechanical ventilation compared to 14 (46.7%) out of 30 in placebo group but the difference was not statistically significant. Although there were a greater number of moderate cases in placebo group, invasive ventilation requirement (and NIV requirement) was more in this group, thus it could be considered that vitamin C might have a role in reducing the severity of disease. The need for vasopressor therapy was higher in intervention arm 33.3% compared to 26.7% in placebo but not significant statistically. The secondary outcomes of the study such as improvement in organ failure score (qSOFA Score), fall in level of inflammatory markers, improvement in respiratory index (pO2/fiO2 ratio), need for mechanical ventilation and need for vasopressors also shown encouraging results but not up to the statistically significant level due to moderate dosage of the drug and small sample size. Conclusion: In the current study, by the observations and results of the double-blind placebo controlled randomised trial, we concluded that as the primary outcome of the study, there was reduction in In-hospital mortality and need for mechanical ventilation in the vitamin C intervention group compared to placebo, although these results did not reach statistical significance due to small sample size and use of moderate dose of IV vitamin C. The secondary outcomes of the study such as improvement in organ failure score (qSOFA Score), fall in level of inflammatory markers, improvement in respiratory index (pO2/fiO2 ratio), need for mechanical ventilation and need for vasopressors also shown encouraging results but not up to the statistically significant level due to moderate dosage of the drug and small sample size. In summary, high dose of intravenous vitamin C may reduce inflammatory reaction, improve oxygen support status, and reduce mortality in COVID-19 patients, without adverse events. High dose intravenous vitamin C may be a promising therapy for patients of moderate to severe COVID-19.